Analysis of the effects of dietary fat on body and skin lipids of hamsters by Raman spectroscopy1. Issue 12 (21st June 2015) - Meksiarun, Phiranuphon; Maeda, Yui; Hiroi, Tatsuya; Andriana, Bibin B.; Sato, Hidetoshi
<x xml:space="preserve">Abstract</x> A ball lens installed hollow optical fiber Raman probe (BHRP) was applied for the noninvasive analysis of skinlipids in hamsters.